Seeing through Black Mirror: Future Society and Architecture - M. Galieh Gunagama (Journal of Architectural Research and Design Studies, 2019)
Black Mirror is a series of sci-fi anthology that since it first aired in 2011, has been widely discussed because of its depiction of issues on futuristic technology and its prediction about the future society. Architecture, as a form of social expression, cannot be separated from the community that existed at a time. Through the scenario in Black Mirror, the future of architecture is discussed in this paper.This paper uses analysis of future scenarios as a basis for formulating possible community conditions. The discussion in this paper includes the state of technology and society in the future described in the series, the forms of future scenarios in its narrative, and technology that affects architectural design in the future.The issues in the Black Mirror include human impulse, sensory perception, automation, memory, and cognition. The architectural design in the future depends heavily on how humans and society behave towards technological sophistication that might occur. The diminishing physical sensation will have a significant impact on how the design is formulated.Keywords: black mirror, future of architecture, scenario analysis, technology